Continuity and change in the Australian minimum wage setting system: The legacy of the commission - Waring, P.; Burgess, John (Sage Publications Ltd., 2011)
Australia has a long history of institutional minimum wage determination. We examine the features and the changes in the minimum wages system. We identify its enduring characteristics, its place the Australian system in an international context and see where Fair Work Australia is located in relation to previous arrangements. We ask why a minimum wage system is still required and we examine the legacy of the Australian Industrial Relations Commission and its predecessors in minimum wage determination.